Meeting notes: 11 April 1938 - -, - (Proceedings of the Society of Antiquaries of Scotland, 1938)
Before the meeting began, an obituary was read for Honorary Fellow and frequent contributor to the Proceedings Dr John Graham Callander. This is followed by the meeting notes for 11 April 1938.